2015
DOI: 10.2146/ajhp140191
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of free fraction serum valproic acid concentrations between inpatients and outpatients

Abstract: The median free fraction of valproic acid was significantly higher in inpatients than in outpatients. Low albumin concentration was a predictor of discordance between free and total valproic acid concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
7
11
0
Order By: Relevance
“…Indeed, as confirmed in this study, the binding of VPA to albumin was the major determinant of the unbound VPA concentration. Our results are consistent with those previously published . The latter study showed that low albumin level was the unique independent risk factor for therapeutic discordance between total and unbound VPA concentration by multivariable logistic regression .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, as confirmed in this study, the binding of VPA to albumin was the major determinant of the unbound VPA concentration. Our results are consistent with those previously published . The latter study showed that low albumin level was the unique independent risk factor for therapeutic discordance between total and unbound VPA concentration by multivariable logistic regression .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those previously published . The latter study showed that low albumin level was the unique independent risk factor for therapeutic discordance between total and unbound VPA concentration by multivariable logistic regression . However, hypertriglyceridemia, hyperbilirubinemia, chronic renal failure, hepatic dysfunction, and certain drug interactions are also known to influence the protein binding of VPA .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…30,31 Hypoalbuminemia is a common risk factor for an increased free fraction of valproate. 4,6,32,33 The largest study published to date (including both hospitalized and outpatients) concluded that albumin values less than 3.5 g/L were associated with increased valproate free fractions, the only factor explaining therapeutic discordance between free and total serum valproate concentrations. 33 All patients in our study had albumin concentrations less than 3.7 g/dl.…”
mentioning
confidence: 99%
“…4,6,32,33 The largest study published to date (including both hospitalized and outpatients) concluded that albumin values less than 3.5 g/L were associated with increased valproate free fractions, the only factor explaining therapeutic discordance between free and total serum valproate concentrations. 33 All patients in our study had albumin concentrations less than 3.7 g/dl. Uremia may also alter valproate protein binding, with free fractions of 20% with renal dysfunction compared with 8% without, and a moderate correlation has been observed between valproate free fraction and both serum creatinine and blood urea nitrogen.…”
mentioning
confidence: 99%